Inside architecture - Gregotti, Vittorio (Graham Foundation/MIT Press series in contemporary architectural discourse., 1996)
Inside Architecture is a concise, insightful examination of the role the modernist project has played in late twentieth-century building, as well as an attempt to reconcile the dilemmas and shortcomings of modern orthodoxy with a renewed vision of modernism. Gregotti first identifies the elements of mass culture and public institutions that have led to the deterioration of natural and man-made environments. He then investigates eight issues - precision, technique, monumentality, modification, atopia, simplicity, procedure, and image - that influence the activities of contemporary architects. Gregotti is particularly suspicious of the deconstructivist argument and its heavy reliance on literary models. And he provides an incisive critique of the recent interest in modernist aesthetics, warning against reviving the forms of an old movement without considering the cultural and social criteria that once gave it purpose and meaning.